URGENT PROBLEMS OF THE WESTERN CIRCASSIANS IN THE 21ST CENTURY - BABICH, Irina (CENTRAL ASIA AND THE CAUCASUS, 2014)
The author analyzes the most urgent problems of the Western Circassians (the Shapsugs of the Caucasian Black Sea coast and the Adighe of the Republic of Adigey) caused by the 2014 Winter Olympics in the Krasnodar Territory, as well as the religious context that took shape after the election of the new mufti of the Republic of Adigey in December 2012. The article is based on ethnographic field polls carried out in areas populated by Western Circassians, leading the author to conclude that the government should pay more attention to the social, economic, and cultural problems of the Shapsugs of the Black Sea coastal area and concentrate on preventing Islamic radicalization in the Republic of Adigey.